Lactoferrin/sialic acid prevents adverse effects of intrauterine growth restriction on neurite length: investigations in an in vitro rabbit neurosphere model - Kühne, Britta Anna; Gutierrez-Vázquez, Lara; Sánchez Lamelas, Estela; Guardia-Escote, Laia; Pla, Laura; Loreiro, Carla; Gratacós, Eduard; Barenys, Marta; Illa, Miriam (Frontiers in Cellular Neuroscience, 2023)
In this study we aimed to characterize alterations in neuronal development after intrauterine growth restriction (IUGR) and to discover strategies to ameliorate adverse neurodevelopment effects by using a recently established rabbit in vitro neurosphere culture. IUGR was surgically induced in pregnant rabbits by ligation of placental vessels in one uterine horn, while the contralateral horn remained unaffected for normal growth (control). At this time point, rabbits were randomly assigned to receive either no treatment, docosahexaenoic acid (DHA), melatonin (MEL), or lactoferrin (LF) until c-section. Neurospheres consisting of neural progenitor cells were obtained from control and IUGR pups and comparatively analyzed for the ability to differentiate into neurons, extent neurite length, form dendritic branching or synapses. We established for the very first time a protocol to cultivate control and IUGR rabbit neurospheres not only for 5 days but under long-term conditions up to 14 days under differentiation conditions. We revealed that IUGR significantly increased the neurite length after 5 days cultivation in vitro, a result in good agreement with previous in vivo findings in IUGR rabbits presenting more complex dendritic arborization of neurons in the frontal cortex. Neurospheres obtained from untreated does were exposed in vitro to MEL, DHA, and sialic acid (SA) the main metabolite of LF. MEL, DHA, and SA decreased the IUGR-induced length of primary dendrites, however, only SA was able to reduce the total neurite length to control level in IUGR neurospheres. SA´s parent compound LF was able to prevent abnormal neurite extension after prenatal administration in vivo and was therefore identified as the most promising therapy against IUGR-induced changes in neuronal development.